Religion predicting fertility behaviour of young women in contemporary Germany - Ottenbacher, Martha (Research papers in economics, 2020)
Religion Predicting Fertility Behaviour of Young Women in Contemporary GermanyReligion in contemporary Germany is marked by institutionalized outreach as well as increased pluralisation. Religion can thus play a decisive role in fertility behaviour, despite of secularizing tendencies. Religion may influence the debut and frequency of sexual activity, contraceptive behaviour, cohabitation and marriage. Religious rules on alcohol consumption relate to the likelihood of miscarriages; religious values transmit into abortion laws. This fertility behaviour determines the time when young women have their first live birth. Using data from the German Panel Analysis of Intimate Relationships and Family Dynamics, the paper explores whether being Catholic, Protestant, Muslim or non‐religious shapes fertility patterns of young women in contemporary Germany. The paper extends earlier analyses by integrating miscarriages and abortions, rather than limiting the analysis to births. Results show that Muslims are the youngest when becoming pregnant for the first time. Protestants delay first pregnancy, but once being pregnant, Protestants are more likely to carry their first pregnancy to term rather than having an abortion. With respect to first pregnancy and its outcome, Catholics surprisingly compare to non‐religious women. Against the background of increasing immigration from religiously vivid countries to Germany, the relation between religion and fertility behaviour is likely to remain significant.